Pulmonic Ingressive Speech in Icelandic - Wolf, Kirsten; Beyer, Emily (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2025)
Pulmonic ingressive speech – utterances spoken on the in-breath – is a common feature of many languages including Icelandic. This paper presents findings from a survey-based study conducted in Iceland and in Icelandic-speaking communities in North America on the use of ingressive speech in Icelandic. It includes a general inquiry into the phenomenon in Icelandic and addresses three hypotheses. Results of the survey did not fully confirm our first hypothesis—that ingressive speech continues to be used in Icelandic and that it is used primarily by females. Although it is still used, survey respondents reported that ingressive speech was used about the same by males as by females in both Iceland and North America. However, participants reported hearing it somewhat more in females. Our second hypothesis – that its use is on the wane – was only confirmed by the North American respondents’ reports. Our third hypothesis – that ingressive speech is non-existent in North American Icelandic was not confirmed by the survey results